Preparation of Fe3O4/HAp nanoparticles from eggshells with highly adsorption capacity for methylene blue - Luong, Huynh Vu Thanh; Nguyễn, Ngọc Hân; Khưu, Gia Hân; Bùi, Yến Pha; Thiều, Quang Quốc Việt; Ngo, Truong Ngoc Mai; Tran, Thi Bich Quyen (Can Tho University Journal of Science, 2022)
Multifunctional materials have become one of the most interesting research subjects in recent years. Hydroxylapatite (HAp) coating on the surface of iron oxide (Fe3O4) nanoparticles allow to obtain material with adsorbable and magnetic properties. This study aims to salvage recycled eggshell to successfully produce adsorbent nanoparticles and evaluate treatment ability of methylene blue (MB) dyes in water. The magnetic nanomaterial was synthesized by a simple and inexpensive method. The X-ray diffraction technique was employed to characterize the structure of nanoparticles. The as-synthesized nanoparticles were analyzed by Fourier transform infrared spectroscopy technique to determine the presence of functional groups and bonds in the molecule. The surface morphology of as-synthesized Fe3O4/HAp nanoparticles was studied by transmission electron microscopy. The magnetic properties of Fe3O4 nanoparticles and Fe3O4/HAp nanoparticles were evaluated by vibrating sample magnetometer technique. The typical synthesized-HAp were dispersed rod-like particles with about 10 nm in width and 50 nm in length, the other part of final material was dispersed in spherical shape and their magnetism was 16.2 emu.g-1. The adsorption of MB was conducted with 89.6% yield at pH 8.